LES DIFFICULTES LINGUISTIQUES DANS L’HARMONISATION DES SYSTEMES JURIDIQUES DANS L’UNION EUROPEENE A TRAVERS L’EXAMPLE DES DIRECTIVES PORTANT SUR LES GARANTIES PROCEDURALES EN MATIERE PENALE - de Laforcade, Agata (Comparative Legilinguistics, 2021)
Multilingual writing of European directives is faced with a few linguistic difficulties, like choosing an appropriate legal terms. All linguistic versions shall reflect the same content event though the legal system of each Member State is different and some legal concept do not have an equivalent in other legal systems. In this way, legal writing of European Directive is a very complex subject both from legal and linguistic perspective. The aim of this article is to discuss different linguistics difficulties that could appear during the harmonisation of criminal proceedings in European Union, where multilingualism is a key value and to analyse the possible solutions, when dealing with those difficulties. It seems that even if multilingualism is a big challenge to European Union, it could have a positive influence on the quality of European legislation.